1980
DOI: 10.1002/1520-6807(198010)17:4<469::aid-pits2310170409>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic differences between educationally handicapped and learning disabled students

Abstract: Pr~.rhulugv in the Schuul.r PPVT and MSCA with Autistic Children 4691980. 17.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…The first of these confirms some of our expectations concerning sex differences, whereas the second does not. However, because the results of The average scaled score of the WISC data is, however, reliably higher than that of the the Eno & Woehlke (1980) study so closely resemble the findings made in a large scale (n = 1550; boys = 1075, girls = 479, but as yet unpublished, investigation carried out by one of our own graduate students (Tittemore, 1983), their study demands further analysis here.…”
Section: Sex Differencesmentioning
confidence: 59%
See 2 more Smart Citations
“…The first of these confirms some of our expectations concerning sex differences, whereas the second does not. However, because the results of The average scaled score of the WISC data is, however, reliably higher than that of the the Eno & Woehlke (1980) study so closely resemble the findings made in a large scale (n = 1550; boys = 1075, girls = 479, but as yet unpublished, investigation carried out by one of our own graduate students (Tittemore, 1983), their study demands further analysis here.…”
Section: Sex Differencesmentioning
confidence: 59%
“…= 14, P < 0.025, one-tailed test), and hence supports our hypothesis that sex is one of the sources of variance that serves to determine whether a test-specific or a more general deficit appears in the intelligence test performance of LD children. Our hypothesis, therefore, seems to have enough support from the intelligence test data of adults with unilateral brain damage (Inglis & Lawson, 1982a), from the Eno & Woehlke (1980) paper, from an as yet unpublished study by Tittemore (1983), and from the above correlational analysis to merit further consideration and exploration.…”
Section: J S Lawson and James Inglismentioning
confidence: 64%
See 1 more Smart Citation
“…The rank order of the betas for the girls (see Table 4) shows considerable similarity to that of boys with a notable exception. As was true for boys, the Performance subtests were generally better predictors of girls' Full Scale IQs than were Verbal subtests with Coding being the strongest pre- (Bom, 1994;Carvajal et al, 1992;Eno & Woehlke, 1980;Kaufman & Doppelt, 1976;Smith et al, 1989) and the WISC-III (Slate, 1997(Slate, , 1998Slate & Fawcett, 1996; had indicated that there are gender dif ferences in IQs. The present research was conducted to replicate and extend this research in a sample of students with MR.…”
Section: Prediction Of Lqsmentioning
confidence: 99%
“…For example, research on the WISC-R consistently revealed gender differences in IQs with boys outperforming girls on all subtests except Coding and Digit Span (Bom & Lynn, 1994;Carvajal, Roth, Holmes, & Page, 1992;Eno & Woehlke, 1980;Kaufman & Doppelt, 1976;Lynn & Mulhem, 1991;Slate, Little, Prince, & Blaske, 1995;Smith, Edmonds, & Smith, 1989). Although some researchers argued that these gender differences had no practical significance (e.g., Kaufman & Doppelt, 1976), others argued that the differences were large enough to require separate norms for boys and girls (e.g., Smith et al, 1989).…”
mentioning
confidence: 99%